Effect of temperature rise and ocean acidification on growth of calcifying tubeworm shells ( Spirorbis spirorbis ): an in situ benthocosm approach - S. Ni; I. Taubner; F. Böhm; V. Winde; M. E. Böttcher (Biogeosciences, 2018)
The calcareous tubeworm Spirorbis spirorbis is a widespread serpulid species in the Baltic Sea, where it commonly grows as an epibiont on brown macroalgae (genus Fucus ). It lives within a Mg-calcite shell and could be affected by ocean acidification and temperature rise induced by the predicted future atmospheric CO 2 increase. However, Spirorbis tubes grow in a chemically modified boundary layer around the algae, which may mitigate acidification. In order to investigate how increasing temperature and rising pCO 2 may influence S. spirorbis shell growth we carried out four seasonal experiments in the Kiel Outdoor Benthocosms at elevated pCO 2 and temperature conditions. Compared to laboratory batch culture experiments the benthocosm approach provides a better representation of natural conditions for physical and biological ecosystem parameters, including seasonal variations. We find that growth rates of S. spirorbis are significantly controlled by ontogenetic and seasonal effects. The length of the newly grown tube is inversely related to the initial diameter of the shell. Our study showed no significant difference of the growth rates between ambient atmospheric and elevated (1100 ppm) pCO 2 conditions. No influence of daily average CaCO 3 saturation state on the growth rates of S. spirorbis was observed. We found, however, net growth of the shells even in temporarily undersaturated bulk solutions, under conditions that concurrently favoured selective shell surface dissolution. The results suggest an overall resistance of S. spirorbis growth to acidification levels predicted for the year 2100 in the Baltic Sea. In contrast, S. spirorbis did not survive at mean seasonal temperatures exceeding 24 °C during the summer experiments. In the autumn experiments at ambient pCO 2 , the growth rates of juvenile S. spirorbis were higher under elevated temperature conditions. The results reveal that S. spirorbis may prefer moderately warmer conditions during their early life stages but will suffer from an excessive ...